2016
DOI: 10.1186/s12870-016-0749-9
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiling of marker genes responsive to the defence-associated phytohormones salicylic acid, jasmonic acid and ethylene in Brachypodium distachyon

Abstract: BackgroundBrachypodium distachyon is a promising model plants for grasses. Infections of Brachypodium by various pathogens that severely impair crop production have been reported, and the species accordingly provides an alternative platform for investigating molecular mechanisms of pathogen virulence and plant disease resistance. To date, we have a broad picture of plant immunity only in Arabidopsis and rice; therefore, Brachypodium may constitute a counterpart that displays the commonality and uniqueness of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
66
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 59 publications
3
66
0
1
Order By: Relevance
“…avenae . The Pathogenesis-related ( PR ) genes PR1 and PR5 were upregulated in response to all rust isolates and given that PR1 is a key marker gene of SA signaling (Kouzai et al 2016; Sels et al 2008), this further supports that the activation of SA-dependent defense responses may contribute to the phenotypes observed in B. distachyon and B. hybridum during P. coronata f. sp. avenae infection.…”
Section: Discussionsupporting
confidence: 54%
“…avenae . The Pathogenesis-related ( PR ) genes PR1 and PR5 were upregulated in response to all rust isolates and given that PR1 is a key marker gene of SA signaling (Kouzai et al 2016; Sels et al 2008), this further supports that the activation of SA-dependent defense responses may contribute to the phenotypes observed in B. distachyon and B. hybridum during P. coronata f. sp. avenae infection.…”
Section: Discussionsupporting
confidence: 54%
“…During the infection of R. solani , the SA marker genes BdWRKY45L1 and BdWRKY45L2 were transcribed within 5 and 24 hpi in Bd3‐1 and Gaz‐4, respectively, but not in Bd21 (Fig. c) (Kouzai et al ., ), suggesting the activation of ETI in these R. solani ‐resistant accessions. By contrast, the JA marker BdAOS was clearly induced only in Bd21 (Kouzai et al ., ).…”
Section: Resultsmentioning
confidence: 87%
“…These compounds induced the transcription of BdWRKY45L1 ( Bradi2 g30695 ), a marker gene for SA response, after 24 h of treatment in B. distachyon (Fig. c) (Kouzai et al ., ). The B. distachyon leaves were then treated with these analogs for 24 h, followed by inoculation with R. solani .…”
Section: Resultsmentioning
confidence: 97%
“…Expression profiling of markers for defense-related phytohormones showed that Brachypodium has phytohormone responses more similar to those of rice than of Arabidopsis, suggesting that monocots share a common defense system that is different from that of dicots (Kouzai et al, 2016). Our analyses identified relative higher levels of GA, SA, and JA in the TOL ecotypes when exposed to severe drought with the latter also higher in TOL lines under mild drought.…”
Section: Discussionmentioning
confidence: 99%